An Analytic Hierarchy Process for The Evaluation of Transport Policies to Reduce Climate Change Impacts - Maria Berrittella; A. Certa; M. Enea; P. Zito (Fondazione Eni Enrico Mattei (FEEM), 2007)
Transport is the sector with the fastest growth of greenhouse gases emissions, both in developed and in developing countries, leading to adverse climate change impacts. As the experts disagree on the occurrence of these impacts, by applying the analytic hierarchy process (AHP), we have faced the question on how to form transport policies when the experts have different opinions and beliefs. The opinions of experts have been investigated by a means of a survey questionnaire. The results show that tax schemes aiming at promoting environmental-friendly transport mode are the best policy. This incentives public and environmental-friendly transport modes, such as car sharing and car pooling.
Keywords: C90; Q54; R48; 330; Analytic Hierarchy Process; Transport Policies; Climate Change